Morphometry and Physico-chemical Profiles of Lakes Balinsasayao and Danao (Philippines) - Jones, Stephen R.; Delalamon, Omar J. I. (Silliman Journal, 2024)
Morphometry and profiles of temperature, transparency, dissolved oxygen, pH, alkalinity, orthophosphates, iron, chlorides, and specific conductance were examined for two mountain lakes in Negros Oriental. Profiles suggested the existence of a principal or seasonal storm thermocline near 15m and possilby a monomolimnion at great depths. Thus, the lakes may be meromictic. Dissolved oxygen profile were clinograde, with the boundary between trophogenic and tropholytic waters occuring between 5m and 10 m. Both lakes were poorly buffered and feel within the soft to medium water range. In general, physicochemical conditions and indicated a limited productive potential. Comparisons between lake surface waters, inflows, and suspected outflow are discussed.